A corrosion-resistant crucible for sintering positive electrode materials of lithium batteries and a preparation method thereof

By adding rare earth materials and steelmaking waste slag to the crucible material and adjusting the thermal expansion coefficient, the problem of the crucible for sintering the lithium battery positive electrode material is easily eroded at high temperatures, and the crucible service life is significantly extended and the thermal stability is improved.

CN119285347BActive Publication Date: 2025-04-18FUJIAN JUNGIE NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411358429.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-04-18
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The crucibles for sintering of the existing lithium battery positive electrode material are easily eroded by lithium ions during the high-temperature firing process, resulting in the peeling, cracking and failure, short service life, and frequent replacement, which increases the cost.

Method used

By adding rare earth materials with increased content from the inside to the outside in order to reduce the diffusion rate of lithium ions, and replenishing steelmaking waste slag rich in iron, aluminum and vanadium into the inner layer, adjust the thermal expansion coefficient of the reaction products of the crucible material and lithium ion, reduce surface cracks, and extend service life.

Benefits of technology

The erosion speed of the positive electrode material on the crucible is significantly reduced, the service life of the crucible is extended, the thermal stability is improved, and the service life is increased by more than 60 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005064287100000081
    Figure BDA0005064287100000081
Patent Text Reader

Abstract

An integral corrosion-resistant crucible, the inner surface of the crucible comprises a body layer, a transition layer and a surface layer from the inside to the outside, the thickness of the transition layer is 30-100 μm, and the thickness of the surface layer is 50-200 μm; the body layer, the transition layer and the surface layer contain rare earth element oxides with increasing concentrations, and the surface layer also contains vanadium steel waste slag. The crucible reduces the erosion rate of the positive electrode material and does not stick to the material, ensuring the long-term normal use of the crucible, while increasing the thermal stability of the crucible, extending the service life, and increasing the service life of the crucible by more than 60 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-performance fire-resistant and corrosion-resistant ceramics, and specifically relates to a corrosion-resistant crucible for sintering positive electrode materials of lithium batteries and a preparation method thereof. Technical Background

[0002] Due to its high energy density, long storage life and environmental friendliness, lithium batteries have become the most promising rechargeable secondary batteries and are widely used in various fields of production and life.

[0003] Lithium battery positive electrode materials are essential functional materials in the production process of lithium batteries and require high-temperature sintering synthesis. The lithium-containing raw materials are mixed with oxides of nickel, cobalt, manganese, etc. and placed in a sagger for calcination synthesis at high temperature.

[0004] The level of lithium content in the battery directly determines the performance of the positive electrode material, which directly affects the performance of the battery. Lithium ion corrosion is one of the main reasons for the failure of the sagger used for sintering. Taking into account factors such as energy consumption, environmental protection, and automatic control, crucibles are usually used as containers during sintering. The main raw materials for preparing saggers are mullite, cordierite, and some high-aluminum industrial raw materials. However, the traditional crucibles used for sintering positive electrode materials for lithium batteries are easily corroded during the firing process. Long-term use will cause the crucible to be damaged due to skin shedding, which will not only pollute the product, but also cause the crucible material to fail and cannot continue to be used. At present, the number of uses of commonly used crucibles in China is about 30 times. Due to the short use cycle and frequent replacement, it is a large cost investment for enterprises.

[0005] CN109467422A discloses a special high-cycle ceramic crucible for lithium batteries. The crucible includes a surface working layer and a base layer. The raw materials of the surface working layer include kaolin, white corundum, alumina powder, fused mullite, a binder, spodumene powder, cordierite and water. The raw materials of the base layer include sintered mullite, kaolin, alumina powder, magnesium carbonate, cordierite, talc, fused magnesium aluminum spinel, andalusite, a binder and water. The material of the crucible surface working layer adopts corrosion-resistant material fine particles as the main material, and the material of the base layer adopts a small thermal expansion coefficient, which slows down the time of bottom peeling and sticking, solves the cracking phenomenon of the side and bottom, and the crucible blank has a certain strength.

[0006] CN109320216A discloses a calcium hexaaluminate crucible modified with rare earth oxide based on a lamellar structure. Calcium carbonate and aluminum oxide powder are used as precursors. Through high-temperature synthesis, rare earth oxide lanthanum oxide is added for modification, so that the synthesized calcium hexaaluminate has an ideal lamellar structure. After modification, the unit cell parameters of the calcium hexaaluminate become larger and the lattice is distorted, which is beneficial to the densification of the calcium hexaaluminate, the melting temperature is increased, the high temperature stability is good, the corrosion resistance is strong in an alkaline environment, the expansion coefficient is low, and it is not easy to crack and peel off. It can effectively prevent impurities from mixing in the synthesis of positive electrode materials such as lithium cobalt oxide, and improve the performance of positive electrode materials for lithium batteries.

[0007] CN109400137A discloses a refractory crucible for sintering positive electrode materials of lithium batteries, which is composed of 30-60 parts of mullite, 10-30 parts of cordierite, 5-30 parts of alumina, 0-15 parts of clay, and 0-20 parts of a sintering aid. The median particle size of the mullite, including the first mullite, is 0.5-5 mm, and the median particle sizes of the cordierite and alumina are in the micron level.

[0008] CN114798694A discloses a solid-state denitrification carbon source prepared from restaurant kitchen waste and a preparation method thereof. The restaurant kitchen waste is used as a matrix material, and impurities are removed by sorting, and solid-liquid separation is performed. After the oil is recovered from the liquid phase, the residue and the solid separated from the solid phase are combined and processed together, and the solid is pre-frozen. After the pre-freezing is completed, vacuum freeze-drying is performed. After freeze-drying is completed, the freeze-dried solid is crushed to obtain a solid-state denitrification carbon source, which can be directly used as a carbon source and carrier material for denitrification, thereby strengthening biological denitrification and realizing efficient resource utilization of restaurant waste.

[0009] Various crucible materials used in the prior art have not been able to significantly improve both the service life and the stability during use. It is an urgent need in the industry to develop a crucible that is chemically stable, not prone to peeling during sintering, and has a long service life. Summary of the invention

[0010] The main reason for the failure of the crucible is that the thermal expansion coefficient of the product of the reaction between lithium ions and the crucible material does not match the thermal expansion coefficient of the crucible raw material, which leads to peeling, flaking and cracking of the crucible. In order to overcome the defects of the above-mentioned prior art, the present invention increases the rare earth materials in the crucible material with increasing content from the inside to the outside, thereby reducing the diffusion rate of lithium ions on the surface of the crucible material. In addition, by adding steelmaking waste slag rich in iron, aluminum and vanadium to the inner layer of the crucible, the tolerance of the crucible material to lithium ions is further improved, and the difference between the thermal expansion coefficient of the product of the reaction between lithium ions and the crucible material and the crucible body is adjusted to reduce the generation of cracks on the crucible surface, thereby extending the service life of the crucible.

[0011] The invention discloses an integral corrosion-resistant crucible, the inner surface of the crucible comprises a body layer, a transition layer and a surface layer from inside to outside, the thickness of the transition layer is 30-100 μm, and the thickness of the surface layer is 50-200 μm.

[0012] The main layer includes the following components in weight percentage: 10-20% cordierite, 15-29% fused magnesia-alumina spinel, 5-15% mullite, 5-15% white corundum, 5-10% andalusite, 2-8% kaolin, 10-30% α-alumina, 2-20% potassium feldspar and 5-10% rare earth oxides, wherein the rare earth oxides include Y2O3 and HfO2.

[0013] The transition layer comprises the following components in weight percentage: 5-15% of white corundum, 20-30% of fused magnesium aluminum spinel, 20-30% of alpha-alumina, 10-20% of cordierite, 5-10% of mullite, and 5-10% of rare earth oxide.

[0014] The surface layer comprises the following components in parts by weight: 25-40% of vanadium steel waste slag, 20-50% of alpha-alumina, 10-20% of white corundum, 10-20% of rare earth oxide, and 1-10% of zirconium oxide.

[0015] The average particle size of the rare earth oxide is 50-100nm, more preferably 60-70nm; the average particle size of the vanadium steel waste slag is 100-300nm, more preferably 150-200nm; the particle size of other components is 1-100μm, more preferably 10-30μm; the content of vanadium pentoxide in the vanadium steel waste slag is 10-20%, more preferably 15-18%.

[0016] The mass ratio of Y2O3 and HfO2 in the rare earth oxide is 0.2-5:1, more preferably 0.5-2; the average particle size of Y2O3 and HfO2 is 10-200nm, more preferably 50-100nm, and most preferably 70-80nm.

[0017] A method for preparing a crucible comprises the following steps:

[0018] (1) Mix the raw materials of the body layer according to the proportions, and add a binder and water;

[0019] (2) forming in a mold;

[0020] (3) Firing at 800-1000°C to obtain a green embryo;

[0021] (4) preparing a transition layer slurry according to the raw material ratio, and coating the transition layer slurry on the blank to obtain a blank coated with the transition layer slurry;

[0022] (5) firing the green blank coated with the transition layer slurry obtained in step (4) at 800-1000° C. to obtain a double-fired crucible;

[0023] (6) preparing a surface layer slurry according to the raw material ratio, and coating the surface layer slurry on the twice-fired crucible obtained in step (5) to obtain a crucible embryo coated with a surface layer;

[0024] (7) Firing the crucible blank coated with the surface layer obtained in step (6) at 1650-1750° C. to obtain a corrosion-resistant crucible.

[0025] The binder in step (1) is one of water glass and silica gel, and its added amount is 0.1-2wt% of the raw material of the main body layer, and more preferably 0.3-0.5%. The raw material of the main body layer is the dry material constituting the main body layer; the added amount of water is 10-20% of the raw material of the main body layer; the molding in step (2) is compression molding, and the compression pressure is 1-10MPa; the firing time in step (3) is 1-12h, and more preferably 6-9h.

[0026] In step (4), an adhesive may or may not be added. Preferably, an adhesive is added. The adhesive is polyvinyl alcohol, and the amount added is 0.1-0.5% of the transition layer raw material, more preferably 0.2-0.3%; the amount of water added is 50-100% of the transition layer raw material, more preferably 50-60%.

[0027] The firing time in step (5) is 24-36 hours, more preferably 30-32 hours.

[0028] In step (6), an adhesive may or may not be added, preferably an adhesive is added, and the adhesive is polyvinyl alcohol, and the amount added is 0.1-0.5% of the surface layer raw material, more preferably 0.2-0.3%; the amount of water added is 50-100% of the transition layer raw material, more preferably 50-60%.

[0029] The firing time in step (7) is 36-48 hours, more preferably 40-42 hours.

[0030] Another aspect of the present invention is to protect the use of the crucible in firing the positive electrode of a lithium battery.

[0031] The present application arranges a transition layer and a surface layer on the inner surface of the crucible, and increases the concentration of rare earth oxides in the transition layer and the surface layer by a gradient. As the crucible is used more and more times, lithium ions gradually penetrate into the surface layer of the crucible, and the rare earth oxides in the surface layer form composite oxides with the lithium ions. The thermal expansion coefficient of the composite oxide is substantially the same as that of the transition layer. The addition of vanadium steel waste slag can reduce the penetration rate of lithium ions, thereby ensuring that the crucible will not undergo a significant change in expansion coefficient after repeated use, thereby extending the number of times the crucible is used.

[0032] The beneficial effects of the present invention are: reducing the erosion rate of the positive electrode material on the crucible and preventing the material from sticking, thereby ensuring the long-term normal use of the crucible, while increasing the thermal stability of the crucible, extending the service life, and increasing the service life of the crucible by more than 60 times. Example

[0033] Example 1

[0034] An integral corrosion-resistant crucible, the inner surface of the crucible comprises a body layer, a transition layer and a surface layer from the inside to the outside, the thickness of the transition layer is 100 μm, and the thickness of the surface layer is 200 μm;

[0035] The main layer includes the following components in weight percentage: 15% cordierite, 29% fused magnesia alumina spinel, 15% mullite, 11% white corundum, 6% andalusite, 4% kaolin, 10% α-alumina, 5% potassium feldspar and 5% rare earth oxides, wherein the rare earth oxides include Y2O3 and HfO2, wherein the mass ratio of Y2O3 to HfO2 is 0.5.

[0036] The transition layer comprises the following components in weight percentage: 15% white corundum, 29% fused magnesium aluminum spinel, 21% α-alumina, 20% cordierite, 7% mullite, and 8% rare earth oxide.

[0037] The surface layer comprises the following components in parts by weight: 35% of vanadium steel waste slag, 40% of α-alumina, 10% of white corundum, 12% of rare earth oxides, and 3% of zirconium oxide.

[0038] The method for preparing a crucible comprises the following steps:

[0039] (1) Mixing the raw materials of the main body layer according to the proportions and adding a binder and water, wherein the binder is water glass, and the amount of the added binder is 2wt% of the raw materials of the main body layer; the amount of the added water is 20% of the raw materials of the main body layer;

[0040] (2) Molding in a mold with a molding pressure of 1 MPa;

[0041] (3) Firing at 800-1000°C for 12 hours to obtain a green embryo;

[0042] (4) preparing a transition layer slurry according to the raw material ratio, coating the transition layer slurry on the blank to obtain a blank coated with the transition layer slurry; adding a binder of polyvinyl alcohol in an amount of 0.2% of the transition layer raw material; and adding water in an amount of 50% of the transition layer raw material;

[0043] (5) firing the green blank coated with the transition layer slurry obtained in step (4) at 800-1000° C. for 24 hours to obtain a double-fired crucible;

[0044] (6) preparing a surface layer slurry according to the raw material ratio, and coating the surface layer slurry on the double-fired crucible obtained in step (5) to obtain a crucible embryo coated with a surface layer; adding a binder polyvinyl alcohol, the amount of which is 0.3% of the raw material of the surface layer; and adding water in an amount of 50% of the raw material of the transition layer;

[0045] (7) The crucible blank coated with the surface layer obtained in step (6) is fired at 1650-1750° C. for 42 hours to obtain a corrosion-resistant crucible.

[0046] Example 2

[0047] An integral corrosion-resistant crucible, wherein the inner surface of the crucible comprises a body layer, a transition layer and a surface layer from the inside to the outside, the thickness of the transition layer is 80 μm, and the thickness of the surface layer is 150 μm;

[0048] The main layer includes the following components in weight percentage: 15% cordierite, 29% fused magnesia alumina spinel, 15% mullite, 11% white corundum, 6% andalusite, 4% kaolin, 10% α-alumina, 5% potassium feldspar and 5% rare earth oxides, wherein the rare earth oxides include Y2O3 and HfO2, wherein the mass ratio of Y2O3 to HfO2 is 0.5.

[0049] The transition layer comprises the following components in weight percentage: 15% white corundum, 29% fused magnesium aluminum spinel, 21% α-alumina, 20% cordierite, 7% mullite, and 8% rare earth oxide.

[0050] The surface layer comprises the following components by weight: 35% vanadium steel waste slag, 40% α-alumina, 10% white corundum, 12% rare earth oxides, and 3% zirconium oxide. The vanadium steel waste slag is a metal slag containing vanadium oxide obtained by oxidative blowing of vanadium-containing molten iron during the vanadium extraction process.

[0051] The method for preparing a crucible comprises the following steps:

[0052] (1) Mixing the raw materials of the main body layer according to the proportions and adding a binder and water, wherein the binder is water glass, and the amount of the added binder is 2wt% of the raw materials of the main body layer; the amount of the added water is 20% of the raw materials of the main body layer;

[0053] (2) Molding in a mold with a molding pressure of 1 MPa;

[0054] (3) Firing at 800-1000°C for 12 hours to obtain a green embryo;

[0055] (4) preparing a transition layer slurry according to the raw material ratio, coating the transition layer slurry on the blank to obtain a blank coated with the transition layer slurry; adding a binder of polyvinyl alcohol in an amount of 0.2% of the transition layer raw material; and adding water in an amount of 50% of the transition layer raw material;

[0056] (5) firing the green blank coated with the transition layer slurry obtained in step (4) at 800-1000° C. for 24 hours to obtain a double-fired crucible;

[0057] (6) preparing a surface layer slurry according to the raw material ratio, and coating the surface layer slurry on the double-fired crucible obtained in step (5) to obtain a crucible embryo coated with a surface layer; adding a binder polyvinyl alcohol, the amount of which is 0.3% of the raw material of the surface layer; and adding water in an amount of 50% of the raw material of the transition layer;

[0058] (7) The crucible blank coated with the surface layer obtained in step (6) is fired at 1650-1750° C. for 42 hours to obtain a corrosion-resistant crucible.

[0059] Example 3

[0060] An integral corrosion-resistant crucible, the inner surface of the crucible comprises a body layer, a transition layer and a surface layer from the inside to the outside, the thickness of the transition layer is 100 μm, and the thickness of the surface layer is 200 μm;

[0061] The main layer includes the following components in weight percentage: 15% cordierite, 29% fused magnesia alumina spinel, 15% mullite, 11% white corundum, 6% andalusite, 4% kaolin, 10% α-alumina, 5% potassium feldspar and 5% rare earth oxides, wherein the rare earth oxides include Y2O3 and HfO2, wherein the mass ratio of Y2O3 to HfO2 is 0.5.

[0062] The transition layer comprises the following components in weight percentage: 15% white corundum, 29% fused magnesium aluminum spinel, 21% α-alumina, 20% cordierite, 8% mullite, and 7% rare earth oxide.

[0063] The surface layer comprises the following components in parts by weight: 35% of vanadium steel waste slag, 40% of α-alumina, 10% of white corundum, 10% of rare earth oxide, and 5% of zirconium oxide.

[0064] The method for preparing a crucible comprises the following steps:

[0065] (1) Mixing the raw materials of the main body layer according to the proportions and adding a binder and water, wherein the binder is water glass, and the amount of the added binder is 2wt% of the raw materials of the main body layer; the amount of the added water is 20% of the raw materials of the main body layer;

[0066] (2) Molding in a mold with a molding pressure of 1 MPa;

[0067] (3) Firing at 800-1000°C for 12 hours to obtain a green embryo;

[0068] (4) preparing a transition layer slurry according to the raw material ratio, coating the transition layer slurry on the blank to obtain a blank coated with the transition layer slurry; adding a binder of polyvinyl alcohol in an amount of 0.2% of the transition layer raw material; and adding water in an amount of 50% of the transition layer raw material;

[0069] (5) firing the green blank coated with the transition layer slurry obtained in step (4) at 800-1000° C. for 24 hours to obtain a double-fired crucible;

[0070] (6) preparing a surface layer slurry according to the raw material ratio, and coating the surface layer slurry on the double-fired crucible obtained in step (5) to obtain a crucible embryo coated with a surface layer; adding a binder polyvinyl alcohol, the amount of which is 0.3% of the raw material of the surface layer; and adding water in an amount of 50% of the raw material of the transition layer;

[0071] (7) The crucible blank coated with the surface layer obtained in step (6) is fired at 1650-1750° C. for 42 hours to obtain a corrosion-resistant crucible.

[0072] Example 4

[0073] An integral corrosion-resistant crucible, the inner surface of the crucible comprises a body layer, a transition layer and a surface layer from the inside to the outside, the thickness of the transition layer is 100 μm, and the thickness of the surface layer is 200 μm;

[0074] The main layer includes the following components in weight percentage: 15% cordierite, 29% fused magnesia alumina spinel, 15% mullite, 11% white corundum, 6% andalusite, 4% kaolin, 10% α-alumina, 5% potassium feldspar and 5% rare earth oxides, wherein the rare earth oxides include Y2O3 and HfO2, wherein the mass ratio of Y2O3 to HfO2 is 0.5.

[0075] The transition layer comprises the following components in weight percentage: 15% white corundum, 29% fused magnesium aluminum spinel, 21% α-alumina, 20% cordierite, 7% mullite, and 8% rare earth oxide.

[0076] The surface layer comprises the following components in parts by weight: 35% of vanadium steel waste slag, 40% of α-alumina, 10% of white corundum, 12% of rare earth oxides, and 3% of zirconium oxide.

[0077] The method for preparing a crucible comprises the following steps:

[0078] (1) Mixing the raw materials of the main body layer according to the proportions and adding a binder and water, wherein the binder is water glass, and the amount of the added binder is 2wt% of the raw materials of the main body layer; the amount of the added water is 20% of the raw materials of the main body layer;

[0079] (2) Molding in a mold with a molding pressure of 1 MPa;

[0080] (3) Firing at 800-1000°C for 12 hours to obtain a green embryo;

[0081] (4) preparing a transition layer slurry according to the raw material ratio, coating the transition layer slurry on the blank to obtain a blank coated with the transition layer slurry; the amount of water added is 50% of the transition layer raw material;

[0082] (5) firing the green blank coated with the transition layer slurry obtained in step (4) at 800-1000° C. for 24 hours to obtain a double-fired crucible;

[0083] (6) preparing a surface layer slurry according to the raw material ratio, and coating the surface layer slurry on the second-fired crucible obtained in step (5) to obtain a crucible embryo coated with a surface layer; the amount of water added is 50% of the transition layer raw material;

[0084] (7) The crucible blank coated with the surface layer obtained in step (6) is fired at 1650-1750° C. for 42 hours to obtain a corrosion-resistant crucible.

[0085] Comparative Example 1

[0086] The difference from Example 1 is that the surface layer does not contain vanadium steel waste slag, and the surface layer is composed of 50% α-alumina, 35% white corundum, 12% rare earth oxides, and 3% zirconium oxide.

[0087] Comparative Example 2

[0088] The difference from Example 1 is that the bulk layer, transition layer and surface layer do not contain rare earth elements.

[0089] The body layer includes the following components in weight percentage: 15% cordierite, 29% fused magnesium aluminum spinel, 15% mullite, 11% white corundum, 6% andalusite, 4% kaolin, 10% α-alumina, and 10% potassium feldspar.

[0090] The transition layer comprises the following components in weight percentage: 15% white corundum, 30% fused magnesium aluminum spinel, 25% α-alumina, 20% cordierite, and 10% mullite.

[0091] The surface layer comprises the following components in parts by weight: 35% of vanadium steel waste slag, 45% of α-alumina, 17% of white corundum, and 3% of zirconium oxide.

[0092] Comparative Example 3

[0093] The difference from Example 1 is that the bulk layer, the transition layer and the surface layer all contain 5% rare earth elements.

[0094] The main layer includes the following components in weight percentage: 15% cordierite, 29% fused magnesia alumina spinel, 15% mullite, 11% white corundum, 6% andalusite, 4% kaolin, 10% α-alumina, 5% potassium feldspar and 5% rare earth oxides, wherein the rare earth oxides include Y2O3 and HfO2, wherein the mass ratio of Y2O3 to HfO2 is 0.5.

[0095] The transition layer includes the following components in weight percentage: 15% white corundum, 29% fused magnesium aluminum spinel, 21% α-alumina, 20% cordierite, 10% mullite, and 5% rare earth oxide.

[0096] The surface layer comprises the following components in parts by weight: 35% of vanadium steel waste slag, 40% of α-alumina, 10% of white corundum, 5% of rare earth oxide, and 10% of zirconium oxide.

[0097] Comparative Example 4

[0098] The difference from Example 1 is that the main layer, the transition layer and the surface layer all contain 12% of rare earth elements.

[0099] The main layer includes the following components in weight percentage: 15% cordierite, 29% fused magnesia alumina spinel, 15% mullite, 11% white corundum, 6% andalusite, 4% kaolin, 10% α-alumina, 5% potassium feldspar and 5% rare earth oxides, wherein the rare earth oxides include Y2O3 and HfO2, wherein the mass ratio of Y2O3 to HfO2 is 0.5.

[0100] The transition layer includes the following components in weight percentage: 15% white corundum, 29% fused magnesium aluminum spinel, 21% α-alumina, 20% cordierite, 7% mullite, and 8% rare earth oxide.

[0101] The surface layer comprises the following components in parts by weight: 35% of vanadium steel waste slag, 40% of α-alumina, 10% of white corundum, 12% of rare earth oxides, and 3% of zirconium oxide.

[0102] Comparative Example 5

[0103] The difference from Example 1 is that the surface layer does not contain a transition layer.

[0104] The performance tests were performed on the crucibles prepared in Examples 1-5 and Comparative Examples 1-3. The results are shown in Table 1:

[0105] Table 1

[0106]

[0107]

[0108] The flexural strength is measured using a digital engineering ceramic bending strength tester.

[0109] At the same time, performance tests show that the number of crucible uses is mainly determined by the amount of corrosion-resistant materials, rare earth metals and vanadium steel slag. The setting of the transition layer can reduce the expansion coefficient gap between the coating and the body layer and increase the service life. It is found that the use of rare earth and vanadium steel slag will significantly affect the number of crucible uses.

[0110] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An integral corrosion-resistant crucible, wherein the inner surface of the crucible is a body layer, a transition layer and a surface layer from the inside to the outside, the thickness of the transition layer is 30-100 μm, and the thickness of the surface layer is 50-200 μm; The body layer comprises the following components in weight percentage: 10-20% cordierite, 15-29% fused magnesium aluminum spinel, 5-15% mullite, 5-15% white corundum, 5-10% andalusite, 2-8% kaolin, 10-30% α-alumina, 2-20% potassium feldspar and 5-10% rare earth oxide; The transition layer comprises the following components in weight percentage: 5-15% white corundum, 20-30% fused magnesium aluminum spinel, 20-30% α-alumina, 10-20% cordierite, 5-10% mullite, and 5-10% rare earth oxide; The surface layer comprises the following components in weight percentage: 25-40% of vanadium steel waste slag, 20-50% of α-alumina, 10-20% of white corundum, 10-20% of rare earth oxides, and 1-10% of zirconium oxide; The average particle size of the rare earth oxide is 50-100nm; the average particle size of the vanadium steel waste slag is 100-300nm; the particle size of other components is 1-100μm; the content of vanadium pentoxide in the vanadium steel waste slag is 10-20%; The rare earth oxide comprises Y2O3 and HfO2, and the mass ratio of Y2O3 to HfO2 is 0.2-5:

1.

2. The crucible according to claim 1, characterized in that The average particle size of the rare earth oxide is 60-70nm; the average particle size of the vanadium steel waste slag is 150-200nm; the particle size of other components is 10-30μm; and the content of vanadium pentoxide in the vanadium steel waste slag is 15-18%.

3. The crucible according to claim 1, characterized in that The mass ratio of Y2O3 and HfO2 in the rare earth oxide is 0.5-2; and the average particle size of Y2O3 and HfO2 is 50-100nm.

4. The crucible according to claim 1, characterized in that The average particle size of Y2O3 and HfO2 is 70-80nm.

5. The method for preparing a crucible according to any one of claims 1 to 4, comprising the following steps: (1) Mix the raw materials of the main body layer according to the proportions, and add the adhesive and water; (2) Forming in a mold; (3) Firing for the first time at 800-1000°C to obtain a green embryo; (4) preparing a transition layer slurry according to the raw material ratio, and coating the transition layer slurry on the green preform to obtain a green preform coated with the transition layer slurry; (5) firing the green blank coated with the transition layer slurry obtained in step (4) at 800-1000° C. to obtain a double-fired crucible; (6) preparing a surface layer slurry according to the raw material ratio, and coating the surface layer slurry on the twice-fired crucible obtained in step (5) to obtain a crucible embryo with a coated surface layer; (7) Firing the crucible blank coated with the surface layer obtained in step (6) at 1650-1750° C. to obtain a corrosion-resistant crucible.

6. The method according to claim 5, characterized in that The binder in step (1) is one of water glass and silica gel, and its added amount is 0.1-2wt% of the raw material of the main body layer, and the raw material of the main body layer is the dry material constituting the main body layer; the added amount of water is 10-20% of the raw material of the main body layer; the molding in step (2) is compression molding, and the compression pressure is 1-10MPa; the firing time in step (3) is 1-12h.

7. The method according to claim 6, characterized in that The amount of the binder added in step (1) is 0.3-0.5% of the raw material of the main body layer; the firing time in step (3) is 6-9h.

8. The method according to claim 5, characterized in that In step (4), a binder may or may not be added.

9. The method according to claim 8, characterized in that In step (4), an adhesive is added, wherein the adhesive is polyvinyl alcohol, and the amount added is 0.1-0.5% of the transition layer raw material; and the amount of water added is 50-100% of the transition layer raw material.

10. The method according to claim 9, characterized in that In step (4), the amount of the adhesive added is 0.2-0.3% of the transition layer raw material; the amount of water added is 50-60% of the transition layer raw material.

11. The method according to claim 5, characterized in that The firing time in step (5) is 24-36 hours.

12. The method according to claim 11, characterized in that The firing time in step (5) is 30-32 hours.

13. The method according to claim 5, characterized in that In step (6), a binder may or may not be added.

14. The method according to claim 5, characterized in that The firing time in step (7) is 36-48 hours.

15. The method according to claim 14, characterized in that The firing time in step (7) is 40-42 hours.

16. Use of the crucible according to any one of claims 1 to 4 in firing positive electrodes of lithium batteries.

Citation Information

Patent Citations

  • Manufacturing method of rare earth oxide modified calcium hexaaluminate crucible based on lamellar structure

    CN109320216A

  • Fire-proof crucible for sintering of cathode material for lithium battery and preparation method of fire-proof crucible

    CN109400137A

  • Solid-phase denitrification carbon source prepared from kitchen waste and preparation method of solid-phase denitrification carbon source

    CN114798694A

  • Yttrium oxide-tungsten graded material as well as preparation method thereof and application thereof in manufacturing crucible for rare-earth smelting

    CN106392082A

  • Lithium battery special high-cycle special ceramic crucible and preparation method thereof

    CN109467422A